Oral Medicine and Restorative Dentistry: The Importance of Dental Materials. - Shahzad, Aamir; Kathia, Talha Muhammad; Abbas, Sadia; Kamal, Muhammad Mohsin; Rathore, Ehsan; Iqbal, Ayousha (Journal of Neonatal Surgery, 2025)
Objective: To determine the levels of knowledge, attitudes, and clinical practices in dental practitioners concerning restorative dental materials and to determine factors related to evidence-based material selection. Methodology: A cross sectional study involving 156 dental practitioners was conducted in Dental Materials Department. The sample size was chosen through multistage probability sampling of public hospitals, privately operated clinics as well as academic institutions. The data were gathered in the form of a structured self-administered questionnaire, which included the sections on demographic factors, knowledge about the frequently used restorative materials, attitudes toward the use of evidence-based selection and self-reported clinical practices. The SPSS version 25 was used to analyze the data. Descriptive statistics were used to summarize the knowledge, attitudes, and practices of the participants, and chi-square test and multivariate logistic regression were used to determine predictors of good knowledge. The statistical significance was predetermined as p ≤0.05. Results: Postgraduate-qualified dentists and dentists with over ten years of clinical experience showed higher knowledge as compared to the rest. The views on the evidence-based material choice and minimal invasive methods were good, but the practical implementation was uneven. Composite resin was the most widely used and the application of rubber dams and bioactive materials was not uniform. The analysis of multiple variables revealed that postgraduate qualification (AOR = 2.64), experience longer than 10 years (AOR = 2.11), and attendance at CPD regularly (AOR = 1.87) were important predictors of good knowledge. Conclusion: The level of dental practitioners’ knowledge on restorative materials is moderate to high and depends on education, experience, and CPD involvement. Material selection and clinical outcomes can be improved by enhancing postgraduate training and promoting the use of evidence-based practice.. .